Studi Akumulasi Pigmen β-Cryptoxanthin untuk Membentuk Warna Jingga Buah Jeruk di Daerah Tropika - Sumiasih, Inanpi Hidayati; Arzam, Taruna Shafa; Poerwanto, Roedhy; Efendi, Darda; Agusta, Andria; Yuliani, Sri (Indonesian Society for Horticulture / Department of Agronomy and Horticulture, 2018)
ABSTRACTDegreening is a transformation process on peel which enables it to change color from green to orange on citrus fruits. The orange color of the peel comes from the mixture of carotenoid pigments, such as β-cryptoxanthin and β-citraurin. The pigments contributed in the formation of β-citraurin are β-cryptoxanthin and zeaxanthin. The objectives of this study were (1) to obtain proper degreening temperature in the orange color formation of several citrus varieties, and (2) to identify and determine pigments of β-cryptoxanthin pigment and total chlorophyll content in citrus peel after degreening. This study was conducted at PKHT IPB and LIPI Cibinong from July 2013 to December 2013, and from February 2016 to May 2017. About 100 ppm of ethylene gas was injected into a citrus-containing box using 5 ml syringe, then the box was placed in cool storage at 15 0C, 20 0C and room temperature, for 72 hours. The results showed that the best colors of Keprok Selayar and Keprok Tejakula were obtained by the degreening at 15 0C, in Siam Kintamani it was obtained by degreening at 20 0C. Degreening significantly reduced the total chlorophyll content, and increased β-cryptoxanthin content. The content of β-cryptoxanthin after degreening was 3 folds higher on highland Citrus reticulata than lowland citrus.Keywords: citrus color index, chlorophill, degreening, ethylene, tropical citrusABSTRAKDegreening adalah proses perombakan warna hijau pada kulit jeruk diikuti dengan proses pembentukan warna jingga. Warna jingga adalah campuran antara β-cryptoxanthin dengan β-citraurin. Pigmen yang berkontribusi dalam pembentukan β-citraurin adalah β-cryptoxanthin dan zeaxanthin. Tujuan penelitian ini ialah (1) Mendapatkan suhu degreening yang tepat dalam pembentukan warna jingga pada beberapa varietas jeruk, (2) Identifikasi dan penentuan kadar pigmen β-cryptoxanthin dan kandungan total klorofil pada kulit jeruk setelah degreening. Penelitian ini dilakukan di PKHT IPB dan LIPI Cibinong pada bulan Juli 2013 sampai Desember 2013, dan bulan Februari 2016 sampai Mei 2017. Degreening dilakukan dengan menginjeksikan gas etilen konsentrasi 100 ppm ke dalam wadah tertutup yang berisi jeruk menggunakan syringe 5 ml, kemudian disimpan pada suhu 15 0C, 20 0C dan suhu ruang, selama 72 jam. Hasil penelitian menunjukkan bahwa warna terbaik jeruk Keprok Selayar dan Tejakula diperoleh dengan degreening pada suhu 15 0C, Siam Kintamani diperoleh dengan degreening pada suhu 20 0C. Degreening dapat menurunkan kandungan total klorofil secara tajam, dan terbukti meningkatkan kandungan pigmen β-cryptoxanthin. Kandungan pigmen β-cryptoxanthin setelah degreening 3 kali lebih tinggi pada jeruk keprok dataran tinggi dibandingkan dengan dataran rendah.Kata kunci: citrus color index, degreening, etilen, jeruk tropika, klorofil